2007
DOI: 10.1007/s10267-006-0337-1
|View full text |Cite
|
Sign up to set email alerts
|

Two species of Leptographium isolated from blue-stained sapwood of Pinus khasya and bark beetles in Thailand

Abstract: Two species of Leptographium were isolated from blue-stained sapwood of Pinus khasya and bark beetle galleries in pine trees near Chiang Mai, Thailand. Based on morphological observations, these two species were identifi ed as L. pini-densifl orae and L. yunnanense. This is the fi rst record of these fungi in Thailand. Leptographium yunnanense appeared to be associated with Polygraphus major.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…In this study, L. pini-densifl orae, which is found only in Japan and Thailand (Yamaoka et al 2007) at present, was isolated from T. piniperda, T. minor, C. fulvus, and O. angulatus, which are not root-feeding beetles. Generally, Leptographium species are known to be associated with root-feeding beetles or bark beetles that infest the lower part of trunks (Harrington 1988;Wingfi eld and Gibbs 1991).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, L. pini-densifl orae, which is found only in Japan and Thailand (Yamaoka et al 2007) at present, was isolated from T. piniperda, T. minor, C. fulvus, and O. angulatus, which are not root-feeding beetles. Generally, Leptographium species are known to be associated with root-feeding beetles or bark beetles that infest the lower part of trunks (Harrington 1988;Wingfi eld and Gibbs 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The fourth most prevalent species collected in this study was G. yunnanensis including 39 isolates, 27 of which were vectored by seven mite species. G. yunnanensis was originally described from Tomicus yunnanensis on P. yunnanensis in China ( Zhou et al 2000 ), and was subsequently reported from Polygraphus major on Pinus kesiya in Thailand ( Yamaoka et al 2007 ), and four other pine bark beetle species on P. densiflora in Japan ( Masuya et al 2009 ). Results of the present study have added an additional three beetle species to this list including Cryphales luteus , Polygraphus szemaoensis and an unidentified Polygraphus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Group A included G. koreana , G. yunnanense , H. pinicola and L. truncatum . The first two of these have thus far only been found in countries such as Japan, Korea, Thailand and China ( Zhou et al 2000 , Kim et al 2005a , Masuya et al 2005 , 2009 , Yamaoka et al 2007 , 2008 , Lu et al 2009a ). Hyalorhinocladiella pinicola has been recorded from Canada and Japan ( Jacobs et al 2005 ) and L. truncatum from Africa, North America, Europe and New Zealand ( Wingfield & Marasas 1983 , Hausner et al 2005 , Jacobs et al 2005 ).…”
Section: Discussionmentioning
confidence: 99%